2020
DOI: 10.1108/itp-05-2019-0231
|View full text |Cite
|
Sign up to set email alerts
|

Many hands make light work: towards a framework of digital co-production to co-creation on social platforms

Abstract: PurposeRecent technological advances have enabled consumers and citizens to contribute to organizational processes through co-production and co-creation in ways that challenge traditional co-production. However, the practices and capabilities for value co-creation are less understood, particularly in an increasingly networked social government ecosystem. The purpose of this research is to examine the enablement of new digital co-production practices in social media platforms (SMPs) and theorize SMP-enabled dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…E-participation and the exchange of information on social networks and digital platforms have changed the approach from co-creation to co-design by placing the typology and accessibility of data at the centre. The government can move from a government-centric perspective to a more citizen-centric one by increasing the benefits between the parties; citizens as co-producers can provide their opinions through social media, guaranteeing direct resolution of mutual interests that has a great impact on public value (Alam, 2020;Bracci et al, 2019;Steccolini, 2019). The analysis of social media (such as Twitter) and sentiments increases the administration's narrative and decision-making capacity, although how this approach takes place has not been defined (Akom et al, 2016;Balogun et al, 2020;Chen, 2014).…”
Section: Literature On Popular Reportingmentioning
confidence: 99%
“…E-participation and the exchange of information on social networks and digital platforms have changed the approach from co-creation to co-design by placing the typology and accessibility of data at the centre. The government can move from a government-centric perspective to a more citizen-centric one by increasing the benefits between the parties; citizens as co-producers can provide their opinions through social media, guaranteeing direct resolution of mutual interests that has a great impact on public value (Alam, 2020;Bracci et al, 2019;Steccolini, 2019). The analysis of social media (such as Twitter) and sentiments increases the administration's narrative and decision-making capacity, although how this approach takes place has not been defined (Akom et al, 2016;Balogun et al, 2020;Chen, 2014).…”
Section: Literature On Popular Reportingmentioning
confidence: 99%
“…Co-creation research is dominated by empirical insights concerned with how organisations encourage and leverage brand conversations to enhance brand values and equity (Alam, 2020). France et al (2015) indicated that co-creation behaviours are customer-led and are predicated on pre-existing brand relationships (Sarkar and Banerjee, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These works indicate that co-creation is a shared experience. There is an intrinsic need for participation, personal proximity and a sense belonging (Alam, 2020; Pan, 2020), with this facilitated by a given brand (Akman et al , 2019). This desire for interactivity and social interaction results in a willingness to engage collectively (Jun et al , 2020) and is representative of a literal and metaphoric journey as consumers move towards a more collective consciousness (Akman et al , 2019).…”
Section: Conceptual Framework: Drivers Of Co-creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media and digital technologies are seen as important enablers (Alam 2020;Daneshvar et al 2018;Venugopalan et al 2021), allowing real-time interactions between government and citizens with almost no cost (Meijer 2011). The capacity of new media, a new form of connection between government and citizens, allows new practices of coproduction.…”
Section: Introductionmentioning
confidence: 99%